2019
DOI: 10.5194/isprs-annals-iv-4-w8-139-2019
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Automatic Pointwise Semantic Segmentation of a 3d Urban Scene From Mobile Terrestrial and Airborne Lidar Point Clouds: A Machine Learning Approach

Abstract: <p><strong>Abstract.</strong> Automatic semantic segmentation of point clouds observed in a 3D complex urban scene is a challenging issue. Semantic segmentation of urban scenes based on machine learning algorithm requires appropriate features to distinguish objects from mobile terrestrial and airborne LiDAR point clouds in point level. In this paper, we propose a pointwise semantic segmentation method based on our proposed features derived from Difference of Normal and the features “direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The feature vector generally consists of quantitative values for each feature. For the task of extracting points belonging to our historical building from point clouds, semantic segmentation based on the feature vectors proposed in [38] is chosen to process the input point clouds presented in the previous section. In this work, among others, features such as (i) "directional height above" compares the height difference between a point and its neighbours in eight directions, (ii) "difference of normal" is based on a normal estimation which can better distinguish when vegetation and man-made objects are used.…”
Section: Semantic Segmentation Of Lidar Point Cloud For Object Extractionmentioning
confidence: 99%
“…The feature vector generally consists of quantitative values for each feature. For the task of extracting points belonging to our historical building from point clouds, semantic segmentation based on the feature vectors proposed in [38] is chosen to process the input point clouds presented in the previous section. In this work, among others, features such as (i) "directional height above" compares the height difference between a point and its neighbours in eight directions, (ii) "difference of normal" is based on a normal estimation which can better distinguish when vegetation and man-made objects are used.…”
Section: Semantic Segmentation Of Lidar Point Cloud For Object Extractionmentioning
confidence: 99%
“…Most of classification algorithms, including the Random Forest, rely on local and global descriptors, computed at a point scale, or at a global scale (Hackel et al, 2016;Xing et al, 2019). Such descriptors are usually easy and fast to compute, while providing meaningfull geometrical information.…”
Section: Descriptors Computationmentioning
confidence: 99%
“…The proposed method results in the main overall accuracy of 95%. More recently, Xing et al used the Hackel et al workflow as a basis and developed a more robust workflow by adding a series of features computed based on the difference of normal vectors for better identification [19,20]. Their study demonstrated a 2% improvement on average.…”
Section: Studies Used 3d Point Clouds For Detection and Classificationmentioning
confidence: 99%